2017
DOI: 10.1021/acs.bioconjchem.7b00190
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced and Prolonged Cell-Penetrating Abilities of Arginine-Rich Peptides by Introducing Cyclic α,α-Disubstituted α-Amino Acids with Stapling

Abstract: Cell-penetrating peptides are receiving increasing attention as drug delivery tools, and the search for peptides with high cell-penetrating ability and negligible cytotoxicity has become a critical research topic. Herein, cyclic α,α-disubstituted α-amino acids were introduced into arginine-rich peptides and an additional staple was provided in the side chain. The peptides designed in the present study showed more enhanced and prolonged cell-penetrating abilities than an arginine nonapeptide due to high resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…[24] The chiral acetal moiety in the (R,R)-Ac 4 c 3BD was changeable and may also be used for low pH-triggerings tructural changes. [25] Therefore, precisely elucidated helical secondary structures may be invaluable for designing organo-catalysts, [26] cell-penetrating peptides, [27] and targetbinding peptides. [24] .…”
mentioning
confidence: 99%
“…[24] The chiral acetal moiety in the (R,R)-Ac 4 c 3BD was changeable and may also be used for low pH-triggerings tructural changes. [25] Therefore, precisely elucidated helical secondary structures may be invaluable for designing organo-catalysts, [26] cell-penetrating peptides, [27] and targetbinding peptides. [24] .…”
mentioning
confidence: 99%
“…Oba and co-workers developed novel CPPs using a combination of a stapled crosslinker and dAA residues in an Arg-based peptide. [28] The stapled peptide formed a stable α-helical structure and exhibited greater cell-membrane permeability than the unstapled peptides. The stapled peptide also displayed higher cell-membrane permeability under serum-free conditions than under serum-containing conditions, indicating that stapled CPPs exhibit promising cell-membrane permeability, regardless of their resistance to proteolytic enzymes.…”
Section: Side-chain Staplingmentioning
confidence: 99%
“…The stapled peptide also displayed higher cell-membrane permeability under serum-free conditions than under serum-containing conditions, indicating that stapled CPPs exhibit promising cell-membrane permeability, regardless of their resistance to proteolytic enzymes. [28] Verdine and co-workers reported that stitched peptides, which have two hydrocarbon cross-linkers in their side chains at the i, i + 4, and i + 11 positions, formed more stable helical structures than the peptides containing a single staple. [29] Thus, stitched CPPs have been developed by introducing olefin-bearing amino acids into R9 at the i, i + 4, and i + 11 positions, before olefin-metathesis was performed.…”
Section: Side-chain Staplingmentioning
confidence: 99%
“…α,α‐Disubstituted α‐amino acids (dAAs) have an additional alkyl substituent at the α position of an α‐amino acid instead of a hydrogen atom . dAA‐containing peptides also exhibit metabolic stability against proteases . Homopeptides composed of α‐methylated and cyclic dAAs were reported to form a stable helical structure, even over a short sequence .…”
Section: αα‐Disubstituted α‐Amino Acidsmentioning
confidence: 99%
“…[20] dAA-containing peptides also exhibit metabolic stability against proteases. [21] Homopeptides composed of a-methylated and cyclic dAAs were reported to form as table helical structure, even over as hort sequence. [20] Furthermore, the introduction of a-methylated and cyclic dAAs into peptides composed of a-aminoa cids often leads to a marked conformational changef rom ar andomc oil to ah elical structure.…”
Section: G-amino Acidsmentioning
confidence: 99%